Effects of passthrough pricing rules on gas purchase decisions from different basins - Navajas, Fernando (1998)
The paper is organised as follows. Before we proceed to the main analysis, we present the reader a brief introduction to the institutional setting of the gas industry and natural gas regulation in Argentina. In section 3 we show reference results for a basic model with only one-basin and two final markets (regulated and unregulated). In section 4 we present a model of two basins and two markets adapted to the argentine case. In section 5 we address the consequences of moving from a variable to a fixed weights rule. Finally section 6 concludes and draws the main implications in light of some evidence obtained from the argentine case.